Training on the Utilization of Household Organic Waste as Compost Fertilizer in Tamansuruh Village - Jefry Aulia Martha; Mohammad Hilfi Azra Dzikrulloh; Reta Lola Oftaviana; Hafifatus Syabila (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
Problems related to waste, waste processing, to environmental pollution will become a big problem if not handled properly. These problems can be solved with economical solutions such as the utilization of household organic waste into compost. This program aims to help the community to be able to produce compost from household organic waste in Tamansuruh Village, which is one of the villages in Glagah District, Banyuwangi Regency. Where the problems faced by the villagers are the lack of information and limited knowledge about new innovations in making compost. The process used in this composting is anaerobically assisted by a simple composter. To achieve this goal, the method used is preparation in the form of observation of problems, implementation in the form of socialization, training, and direct practice, and evaluation. The result of this activity is in the form of compost derived from household organic waste made by residents and for the residents themselves. Making compost is also able to increase the innovation power of residents in managing household organic waste and increase productivity in the field of agriculture.